2022
DOI: 10.1200/jco.21.01657
|View full text |Cite
|
Sign up to set email alerts
|

BRE12-158: A Postneoadjuvant, Randomized Phase II Trial of Personalized Therapy Versus Treatment of Physician's Choice for Patients With Residual Triple-Negative Breast Cancer

Abstract: PURPOSE Patients with triple-negative breast cancer (TNBC) with residual disease after neoadjuvant chemotherapy (NAC) have high risk of recurrence with prior data suggesting improved outcomes with capecitabine. Targeted agents have demonstrated activity across multiple cancer types. BRE12-158 was a phase II, multicenter trial that randomly allocated patients with TNBC with residual disease after NAC to genomically directed therapy versus treatment of physician choice (TPC). PATIENTS AND METHODS From March 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…In their article in the Journal of Clinical Oncology , Schneider et al 1 reported the results of the BRE12-158 trial, which confirmed that directed therapy was not superior to the treatment of physician's choice (TPC) for patients with residual triple-negative breast cancer after neoadjuvant chemotherapy. Despite the impressive results, it may have some points to consider for further discussion.…”
Section: To the Editormentioning
confidence: 99%
“…In their article in the Journal of Clinical Oncology , Schneider et al 1 reported the results of the BRE12-158 trial, which confirmed that directed therapy was not superior to the treatment of physician's choice (TPC) for patients with residual triple-negative breast cancer after neoadjuvant chemotherapy. Despite the impressive results, it may have some points to consider for further discussion.…”
Section: To the Editormentioning
confidence: 99%
“…The theoretical advantage for olaparib use includes targeting a known tumour susceptibility in a selected population, leading to an improved response and improved tolerability compared to standard cytotoxics. Interestingly, a phase 2 trial that assessed the value of molecularly targeted postneoadjuvant treatment vs choice of clinician in TNBC patients with residual disease did not demonstrate the superiority of this approach ( 86 ). Despite the limitations with regard to the primary outcome, an example was set for biomarker-driven clinical trials and the use of ctDNA in optimising the selection of biomarker-treatment partners.…”
Section: Overall Approach To the Treatment Of Early Stage Tnbcmentioning
confidence: 99%
“…We appreciate the interest in our work 1 highlighted by the letter from Nozawa et al 2 We are also grateful for the opportunity to reflect on the interesting points highlighted.…”
mentioning
confidence: 90%